(untitled) (Historia, 2021)
On a theoretical level, popular music records serve as artefacts of the social and cultural networks in which their particular performers are embedded. Seen from this perspective, the appearance of the earliest Afrikaans gramophone records coincided with a crucial juncture in the formation of Afrikaner identity, as well as the development of the language itself. This article is a forensic investigation into the socio-political contexts in which the first Afrikaans gramophone records were produced. Its sources include updated discographic catalogues that have led to the discovery of listings of a number of recordings that pre-date the previously earliest known Africana and Afrikaans records. Most of the first Africana recordings were of the national anthems of the two Boer republics during and shortly after the Anglo-Boer War (1899-1902) and sung by Dutch singers. The first Afrikaans recordings by people beginning to define themselves as Afrikaners, date back to 1906, while local advertisements for Afrikaans records began to appear in 1910. This article will seek to explore the link between these recordings and claims for nationhood based on the linguistic identity of a key group of white Afrikaans speakers. Op ’n teoretiese vlak funksioneer populêre musiek albums as artefakte van die sosiale en kulturele netwerke waaraan die kunstenaars gekoppel is. Gesien van uit hierdie perspektief, val die eerste Afrikaanse grammofoonplate saam met ’n belangrike stadium in die ontwikkeling van Afrikaner identiteite, asook die ontwikkeling van Afrikaans as taal. Hierdie artikel is ’n forensiese ondersoek wat fokus op die sosio-politieke kontekste waarin die eerste Afrikaanse grammofoonplate gemaak is. Bronne sluit in opgedateerde diskografiese katalogusse wat gelei het tot die ontdekking van lyste van opnames wat ouer is as die vroegste bekendste Africana en Afrikaanse plate. Die meeste van die eerste Africana opnames was van die nasionale volksliedere van die twee Boere republieke tydens, en kort na, die Anglo-Boereoorlog (1899-1902) en is gesing deur Hollandse sangers. Die eerste Afrikaanse opnames deur mense wat begin het omhulself te definieer as Afrikaners dateer uit 1906, terwyl plaaslike advertensies vir Afrikaanse plate begin verskyn in 1910. Hierdie artikel beoog om die verhouding tussen hierdie opnames en eise tot nasieskap, gebaseer op die linguistiese identiteit van ’n sleutelgroep Afrikaners, te verken.